KEANEKARAGAMAN SERANGGA PADA PERKEBUNAN KACANG PANJANG (Vigna sinensis) DI DESA MERITAI KECAMATAN RAMBUTAN KABUPATEN BANYUASIN SUMATERA SELATAN - Dian Mutiara, Dewi Rosanti (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
Research ofÂ  Insect Diversity on long bean (Vigna sinensis) in Meritai Village Rambutan SubdistrictÂ  Â Sumatera Selatan Province, conductedÂ  May till Â Juni 2012, to saw species of long bean insect and its diversity. The research used direct survey method, and data sampling with purpossive in 6 transect and 4 subtransect in 50 m x 20 m areas.Â  The result showed gated 14 species long bean insects and diversity index was medium categhory with Â Hâ value Â 2,12.Â Key words :Â Â  diversity, insect, Â Vigna sinensis